2017
DOI: 10.1111/jdv.14353
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal melanoma: clinical, histological and c‐kit gene mutational profile of 86 French cases

Abstract: This study confirmed that mucosal melanomas are rare and could be difficult to diagnose being often amelanotic and in hidden sites. Most melanomas were thick at the diagnosis, but glans and vulvar melanomas were thinner probably because of their greater visibility. The frequency of the c-kit mutation varied depending on the initial tumour site. In our series, the prognosis was poor, independently from c-kit mutations and the patient's general health and age. The presence of metastasis at diagnosis was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
2
20
0
1
Order By: Relevance
“…15 Male gender, tumour thickness, age, ulceration and advanced tumour stage at initial diagnosis are linked to a less favourable prognosis for mucosal melanoma. [14][15][16][17][18][19][20][21] In the current study, age ≥60, anorectal localization, thickness and advanced tumour stage were identified as significant negative prognostic factors for survival according to the univariate analysis. In the multivariate analysis, older age and advanced tumour stage remained independent significant influence factors for survival.…”
Section: Discussionmentioning
confidence: 59%
“…15 Male gender, tumour thickness, age, ulceration and advanced tumour stage at initial diagnosis are linked to a less favourable prognosis for mucosal melanoma. [14][15][16][17][18][19][20][21] In the current study, age ≥60, anorectal localization, thickness and advanced tumour stage were identified as significant negative prognostic factors for survival according to the univariate analysis. In the multivariate analysis, older age and advanced tumour stage remained independent significant influence factors for survival.…”
Section: Discussionmentioning
confidence: 59%
“…KIT mutation is associated with older age, with CSD melanoma, the mucosal and acrolentiginous forms [13]. As an extreme example, recent data from Slovenia, a neighboring country to Hungary, KIT mutation frequency was found to be 1.3% [11] while an analysis from Italy (UV-and non-UV forms) and France (mucosal only) found~10% [14,15]. One explanation for such discrepancies is the composition of the melanoma cohorts: frequently including mucosal melanomas as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the anatomical features of this area and the frequent deep infiltration explain the difficulty in obtaining disease-free margins after surgical resection, which, to date, represents the treatment of choice for this tumour, associated or not with adjuvant radiotherapy. 2,3 The routine inspection of the oral cavity is mandatory during the dermatological examination to detect early asymptomatic OMM and improve the prognosis of patients with OMM. As dermoscopy improves the diagnostic accuracy of clinical examination, it is necessary to ameliorate this technique in order to overcome the obstacles related to the anatomy of the oral cavity and ensure an examination of its inner part, such as recently suggested by D. Jakhar, MD, and C. Grover, MD.…”
Section: S Caiusmentioning
confidence: 99%
“…Reply to mucosal melanoma: clinical and genetic profile Dear Editor, We appreciated the comment of Solovan et al 1 on our article on mucosal melanoma recently published on the JEADV. 2 The relative rarity of mucosal melanoma contributes to the fact that data concerning this tumour are few and deserve to be published. The authors compared the clinical aspects of our and their population very precisely.…”
mentioning
confidence: 99%